PEMBENTUKAN KARAKTER BAGI ANAK USIA 5-6 TAHUN MELALUI LAGU-LAGU ANAK DITK IT BUNGA HARAPAN SAMARINDA - nurwati nurwati; Aisyah Salsabila (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2020)
The research is entitled "Character Building for Children 5-6 Years Old Through Children's Songs at Kindergarten IT Flower Hope Samarinda". Forming characters  for children through songs is very influential. It is important to teach songs that are appropriate for early childhood so that their characters grow well. The songs that are in Kindergarten IT Flower Hope Samarinda are intended to instill moral character values, as well as attitudes that reflect a sense of caring, discipline and a sense of responsibility in children. These character values   are poured into songs and can   then be applied to children in everyday life. The purpose of this study was to determine the formation of children's characters through children's songs in TK  Bunga Harapan Kindergarten, and what kind of songs are given in order to form good characters in children in TK Bunga Harapan Kindergarten Samarinda.This type of research is research or field with a qualitative descriptive approach. The subjects of this study were the principal, teachers, and students at the Bunga Harapan Kindergarten IT Samarinda. The research methodology used is descriptive qualitative. Data collection methods use observation, interviews, and documentation. Data analysis techniques use data reduction, data presentation and data applications. The validity of the data uses tringulation.The results of this study indicate that the formation of characters for children aged 5- 6 years through children's songs in TK IT Bunga Harapan shows that the songs that are applied can shape the character of responsibility, discipline, and caring, adjusting songs in accordance with the theme of learning. Songs that contain character values are ablution songs, rain songs, professional songs, I am a Muslim song, Baca Hamdalah song, Lahu Santri Kecil, Clearing song, and Recalling song.